Comparison of Clinical Symptoms and Microbiological Results of Otomycosis Due to Candida SP. and Aspergillus SP. Infection in ENT Patients in Denpasar - Putu Rinawati Jayanti; Ketut Wahyudiana Sudana; Made Gita Ratnasari (Journal of Creative Power and Ambition (JCPA), 2026)
Otomycosis is a superficial fungal infection of the external auditory canal that commonly occurs in tropical countries, including Indonesia. The disease is primarily caused by Aspergillus spp. and Candida spp., which exhibit distinct clinical manifestations and therapeutic responses. This study aimed to compare the clinical symptoms and microbiological findings of otomycosis caused by these two fungal pathogens among patients attending the Ear, Nose, and Throat (ENT) Outpatient Clinic in Denpasar. An analytical observational study with a cross-sectional design was conducted involving 41 patients diagnosed with otomycosis. Clinical examinations and ear swab specimens were obtained before antifungal therapy, followed by fungal identification using potassium hydroxide (KOH) preparation, Gram staining, and culture on Sabouraud Dextrose Agar (SDA). The results showed that Aspergillus spp. was the predominant causative organism, whereas Candida spp. was identified in fewer cases. Significant differences in clinical presentation were observed, with Aspergillus infections more frequently associated with severe itching and dark ear discharge, while Candida infections commonly presented with creamy white discharge and ear pain. These findings may support earlier empirical diagnosis and more appropriate antifungal management in resource-limited healthcare settings.